Training in Creating Attractive Promotional Content and Product Marketing Through E-Commerce for MSMEs - Muhamad Imam Agus Faizal (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
Micro, Small and Medium Enterprises (MSMEs) are one of the economic sectors that support people's economic growth. In this era of digitalization, the MSMEs sector is experiencing very rapid development, resulting in changes in marketing methods and forms of product promotion content. Through training activities for creating attractive promotional content and marketing using the e-commerce market place, it is seen that they are able to explore the potential of MSMEs in developing their marketing methods. The method of implementing the activities is carried out in five steps, field observation and preparation, publication and dissemination, outreach, training and mentoring, and monitoring. The training aims to expand product marketing and develop promotional knowledge for the MSMEs in Gantung Village. The series of training activities carried out showed that the participants had a very good understanding of the material, and had the desire to develop their business, as evidenced by the fact that as many as 10 MSMEs actors fully carried out product marketing activities through e-commerce and used attractive promotional content. Meanwhile, other MSME actors are still in the stage of adapting to the new marketing methods used.